Legalitas Keikutsertaan Kabupaten Pemekaran dalam Pemilihan Bupati dan Wakil Bupati Kabupaten Induk - Sabri Guntur (Departement of Mathematics Education, 2023)
The legality of the participation of East Kolaka Regency in the election of regent and deputy regent in Kolaka Regency is based on KPU Circular Number 162/KPU/III/2013 dated March 18 2013 and Letter of the Minister of Home Affairs Number 270/3568/Sj dated July 9 2013 which has been its validity was recognized by the Constitutional Court through the Constitutional Court Decision Number 134/PHPU.D-XI/2013 concerning the East Kalimantan Election Dispute and the Constitutional Court Decision Number 169/PHPU.D-XI/2013 concerning the Kolaka Regency Election Dispute and the legal consequences of the participation of the Kolaka district Timur in the election of the regent and deputy regent in Kolaka district against the election results as the basis for the emergence of legal action from one of the candidate pairs for the Regent and Deputy Regent of Kolaka at the Constitutional Court in decision Number 169/PHPU.D-XI/2013 concerning the Kolaka District Election Dispute.